2022
DOI: 10.1073/pnas.2205784119
|View full text |Cite
|
Sign up to set email alerts
|

A broad and potent neutralization epitope in SARS-related coronaviruses

Abstract: Many neutralizing antibodies (nAbs) elicited to ancestral severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) through natural infection and vaccination have reduced effectiveness to SARS-CoV-2 variants. Here, we show that therapeutic antibody ADG20 is able to neutralize SARS-CoV-2 variants of concern (VOCs) including Omicron (B.1.1.529) as well as other SARS-related coronaviruses. We delineate the structural basis of this relatively escape-resistant epitope that extends from one end of the receptor bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 54 publications
2
33
0
Order By: Relevance
“…More in detail, it is observed that among the investigated ab or nb, m396 (2dd8.pdb, 28 ), REGN10987 (6xdg.pdb, 15 ), and ADG20 (7u2d.pdb, 31 ) bind the stern/stern* portion of the boat‐shaped spike RBD (Table 2 and Figure 5C). The ab Ly‐CoV488 (7kmh.pdb, 26 ), Ly‐CoV481 (7kmi.pdb, 26 ), CT‐P59 (7cm4.pdb, 16 ), and the nb VHH_E (7kn5.pdb), 27 ab Ly‐CoV555 (7kmg.pdb, 26 ), and nb Ty1 (6zxn.pdb), 17 and H11‐H4 (6zh9.pdb), 25 bind the hull/hull* portion of the boat‐shaped spike RBD (Table 2 and Figure 5D).…”
Section: Resultsmentioning
confidence: 95%
“…More in detail, it is observed that among the investigated ab or nb, m396 (2dd8.pdb, 28 ), REGN10987 (6xdg.pdb, 15 ), and ADG20 (7u2d.pdb, 31 ) bind the stern/stern* portion of the boat‐shaped spike RBD (Table 2 and Figure 5C). The ab Ly‐CoV488 (7kmh.pdb, 26 ), Ly‐CoV481 (7kmi.pdb, 26 ), CT‐P59 (7cm4.pdb, 16 ), and the nb VHH_E (7kn5.pdb), 27 ab Ly‐CoV555 (7kmg.pdb, 26 ), and nb Ty1 (6zxn.pdb), 17 and H11‐H4 (6zh9.pdb), 25 bind the hull/hull* portion of the boat‐shaped spike RBD (Table 2 and Figure 5D).…”
Section: Resultsmentioning
confidence: 95%
“…Understanding how SARS-CoV-2 mAbs achieve broad neutralization or are rendered ineffective by viral mutations provides insight not only about natural immunity, but is critical to develop broadly effective therapeutic mAbs and guide vaccine design. 6 , 13 , 22 , 23 , 24 Moreover, defining antibody-antigen interactions is critical for the rapid re-evaluation of existing antibody-based therapeutics toward continuously emerging SARS-CoV-2 variants. This, overlaid with the immuno-genetic makeup of the antibodies shared by a large population further informs our understanding of the public immune response and their antigenic drift from variants.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7 , 13 Such information can be collectively used to fine-tune the immune response focused on broad and potent neutralizing epitopes through antigen design for a universal vaccine. 22 , 24 Recently, based on the information from shared public clonotypes of HIV-1 bnAbs, a V2-apex region-specific immunogen has been successfully designed. 25 …”
Section: Discussionmentioning
confidence: 99%
“…Most SARS-CoV-2 RBD antibodies target three regions: the RBS, the CR3022 site, and the S309 site (Figure 6A). Antibodies targeting the RBS generally exhibit higher frequency and higher neutralization potency due to direct competition with receptor 29 . Almost all commercially available therapeutic neutralizing antibodies (except for Sotrovimab) for COVID-19 treatment target the RBS.…”
Section: Structural Studies Of Group-2 Rbd Broadly Neutralizing Antib...mentioning
confidence: 99%
“…These nAbs exhibit limited cross-reactivity with related coronaviruses and are easily escaped by SARS-CoV-2 variants 26,27 . Class 3 and 4 RBD nAbs are less potent and are less frequently elicited in humans but target relatively more conserved regions of the RBD and exhibit cross-reactivity with VOCs and diverse sarbecoviruses 3,26,[28][29][30][31][32][33][34][35][36][37][38] . Elicitation of nAb responses that target class 3 and 4 RBD sites or the nearby overlapping nAb epitopes are thus more desirable for broad sarbecovirus vaccine strategies.…”
Section: Introductionmentioning
confidence: 99%